Tingkat Kesehatan pada Koperasi Unit Desa Mambal, Kecamatan Abiansemal, Kabupaten Badung - I GUSTI MADE AGUNG YUDA PRAMANA; MADE ANTARA; I KETUT RANTAU (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Health Rating of Mambal Village Unit Cooperative, Abiansemal Sub-District, Badung Regency Based on the Regulation of the Minister of Cooperatives and Small and MediumEnterprises of the Republic of Indonesia No.14/Per M. KUKM/XII/2009, Savings andLoan Cooperative Health Assessment (KSP) is a cooperative condition that deals withaspects of capital, productive asset quality, management, liquidity, efficiency,independence and growth as well as cooperative identity. By reviewing theseconditions, the objectives of this study are The health rating of the Mambal Village UnitCooperative in terms of capital, productive asset quality, management, efficiency,liquidity, independence and growth and cooperative identity in 2015 to 2017. Theresults of the study show that the assessment of the health level of the Mambal VillageUnit Cooperative in 2015-2017 was categorized as quite healthy, because it obtained amean score of 66.64.Suggestions that can be used as input for the Mambal VillageCooperative Unit, namely cooperative managers should be able to increase theacquisition of pre-tax profits by maximizing income through the participation ofmembers in savings and loan activities by maximizing their own capital. In addition,cooperative managers should improve the ability of cooperatives to serve theirmembers.